Answer:
B.3/2
Step-by-step explanation:
I don’t really understand for question 11 to 13
Answer:
x = 5
Step-by-step explanation:
The difference between consecutive terms will be equal , then
a₂ - a₁ = a₃ - a₂ , that is
x + 9 - (3x - 2) = 2x + 5 - (x + 9) ← distribute parenthesis on both sides
x + 9 - 3x + 2 = 2x + 5 - x - 9 , simplify both sides
- 2x + 11 = x - 4 ( subtract x from both sides )
- 3x + 11 = - 4 ( subtract 11 from both sides )
- 3x = - 15 ( divide both sides by - 3 )
x = 5
Answer:
False
Step-by-step explanation:
To find the inverse of a function, switch the variables and solve for y.
The inverse of f(n)=-(n+1)^3:
Answer:
b
Step-by-step explanation:
The equation of a circle centred at the origin is
x² + y² = r² ← r is the radius
The circle shown is centred at the origin and has a radius of 5, thus
x² + y² = 5² ⇒ x² + y² = 25 → b